'I dare not lean to my conceit': Growth in the understanding of contemplative experience in The Cloud of Unknowing. (1st October 2016) - Collins, David L.
Abstract : In this article the nature of the contemplative experience of 'unknowing' is explored, as it is depicted in the classic of Western contemplative literature, The Cloud of Unknowing. Attention is given to the fact that the Cloud author changed his description of unknowing over time, in a manner reflecting growth and deepening of his understanding of the nature of contemplative experience. The article's author also includes mention of a pair of personal meditative experiences, in underscoring the likelihood that considerable humility and open-mindedness are called for in the modern-day incorporation of 'mindfulness' in psychotherapy and programs of well-being.